ANALISIS FORENSIK DIGITAL PADA SKYPE BERBASIS WINDOWS 10 MENGGUNAKAN FRAMEWORK ACPO - Muhammad Rizki Setyawan; Hermansa Hermansa; Muh. Fadli Hasa (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Crime in the world is increasing every year. This is supported by the ease with which people get technology devices and increasingly widespread internet access. The Skype application is one of the tools that can be used to commit cyber crimes. This is due to the increasing number of users. Therefore, in dealing with crimes in cyberspace, digital forensic methods are needed to find digital evidence. This study aims to compare the results of forensic analysis on the Skype application based on Windows 10 with static forensic methods and the Association of Chief Police Officers (ACPO) framework. The results obtained are that Autopsy managed to obtain digital evidence in the form of 15 contact persons, 1 text message, and 9 image files with a performance percentage of 48%. Meanwhile, the Belkasoft Evidence Center forensic tool managed to get digital evidence of 15 contact persons, 2 text messages and the image file could not be found with a performance percentage of 32%. From these results, it can be concluded that Autopsy has a better performance than Belkasoft in finding deleted digital evidencex.